DESTINATION IMAGE AND SHARIA VALUES IN FORMING HALAL TOURISM LOYALTY AND SATISFACTION - Lazavardi Alfarisy; Siti Nur Azizah (Nurul Jadid University, 2026)
This study aims to analyze the influence of destination image and sharia value on tourist satisfaction, with tourist loyalty as a mediating variable in the context of halal tourism in the Special Region of Yogyakarta. The research used a quantitative approach through a survey of 305 Muslim tourists. Data analysis was conducted using multiple linear regression and mediation analysis with the causal steps approach through EViews software. The research results indicate that destination image significantly influences tourist loyalty but does not directly affect tourist satisfaction. Conversely, sharia values positively and significantly impact both tourist loyalty and satisfaction. Tourist loyalty significantly influences satisfaction and acts as a mediator in the relationship between destination image and tourist satisfaction, as well as a partial mediator between sharia values and tourist satisfaction. The results of the mediation test show that tourist loyalty acts as a full mediator in the relationship between destination image and tourist satisfaction, and as a partial mediator in the relationship between Sharia values and tourist satisfaction. This finding emphasizes the importance of Sharia values and loyalty in enhancing halal tourist satisfaction